Peace Values Represented in English Textbook for Tenth-Grade Students: A Critical Discourse Analysis - Santihastuti, Asih; Nur Azizah, Aulia Rahmatika; Ariyanto, Sugeng (EFL Education Journal, 2024)
Peace value is a key to instill learners with good characters. Peace education can readily be integrated into values education as a part of subject through textbook since textbook is mostly used material and every aspect of the textbook has the potential to promote the values. Aiming to explore explicit and implicit messages about peace values in English Textbook for Tenth-Grade Senior High School Students, this study reviews the images of the textbook by revealing the embedded peace values. Critical discourse analysis was conducted to characterize, understand and explain the nature of the textbook’s discourse. The list of peace indicators from Balasooriya (2001) was used to identify kinds of peace values represented in the textbook. The result shows that the contents of peace values, for particularly peace with nature, was seriously under represented while the most represented one is social peace. Consequently, the imbalanced representation of peace values may lead to failure of raising the optimal implementation of the three categories of peace values